Level of heavy metal contamination in agricultural soils and their efects in vegetables in the valley higueras, Huanuco - Riveros Villa, Félix (2017)
In horticultural crops grown on the valley downstream Higueras, farmers developed irrigation activitiesusing the water of the river through Higueras craftsmanship covering approximately 340 hectares.Its use has generated a problem a contamination in horticultural species causing deterioration inthe quality of the products that are mostly consumed fresh. This study was conducted in plantationslettuce (Lactuca sativa), celery (Apium graveolens L), cabbage (Brassica oleracea L) and broccoli(Brassica oleracea italic); in several groing areas downstream of Higueras River, analyzing the levelsof heavy metals such as lead (Pb), cadmium (Cd), arsenic (As) and mercury (Hg) in water, soil andedible part of the plants. It was found that the concentrations of Cd in irrigation water were closeto the limits set by national and international regulations in force, while levels in the soil of the twoplantations were within the normal range. Lettuce and celery at 74 days after transplantation, whit0,40 and 0,30o mg/Kg fresh weight, respectively, were contaminated with Cd surpassing the limit ofthe standard of the European Union. Potential agro-ecological, physiological and sampling reasonsfor this behavior are discussed. In the four vegetables studied, the concentration of Pb exceededthe maximum, allowable concentrations in foods for infants and young children established by theEuropean Union. Generally the highest levels lettuce accumulated heavy metals than other plants.